A myeloperoxidase enhancer drives myeloid cell‐specific labeling in a transgenic frog line. (1st September 2022) - Yamada‐Kondo, Shiori; Ogawa, Ayame; Fukunaga, Miku; Izutsu, Yumi; Kato, Takashi; Maéno, Mitsugu
Abstract: We have identified a myeloid cell‐specific enhancer in the 5′ flanking region of the Xenopus tropicalis myeloperoxidase gene. Transgenic reporter analysis using Xenopus laevis revealed that the expression of GFP was detected in the tail fin macrophages of a swimming tadpole, and the distributions of the GFP‐positive and XL‐2 (a pan‐marker for leukocytes)‐positive cells were mostly overlapping. The GFP‐positive cells in the liver of the transgenic tadpole were localized in the same areas where the myeloid cells were present. Isolation of leukocytes from the peripheral blood cells followed by flow cytometric analysis revealed that the GFP‐positive fraction was specifically enriched in neutrophils with lobulated nuclei. Furthermore, the macrophages purified from the peritoneal cavity were also GFP‐positive. In summary, a transgenic frog line in which the myeloid cells are labeled with GFP provides a useful tool to elucidate the physiological role of myeloid cells of multiple origins in the embryo.